2006
DOI: 10.1007/s00208-006-0032-8
|View full text |Cite
|
Sign up to set email alerts
|

Cartan decomposition of the moment map

Abstract: Abstract. We investigate a class of actions of real Lie groups on complex spaces. Using moment map techniques we establish the existence of a quotient and a version of Luna's slice theorem as well as a version of the Hilbert-Mumford criterion. A global slice theorem is proved for proper actions. We give new proofs of results of Mostow on decompositions of groups and homogeneous spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 24 publications
2
88
0
Order By: Relevance
“…Since G is real-reductive, we may apply the techniques developed in [9] to solve the second problem.…”
Section: Proof Of the Main Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…Since G is real-reductive, we may apply the techniques developed in [9] to solve the second problem.…”
Section: Proof Of the Main Theoremmentioning
confidence: 99%
“…Since the minimal parabolic subgroup Q 0 = M AN is not compatible, we cannot apply the theory developed in [9] Proof. -Recall that the twisted product G × Q X is by definition the quotient space of G×X by the Q-action q ·(g, The claim follows now from the fact that the map , gQ), is a G-equivariant diffeomorphism with respect to the diagonal G-action on X × (G/Q).…”
Section: The Shifting Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Let X ⊂ V be a G-semistable space. From [HS07b] we recall the construction of a slice at a point x ∈ M p in the case X = V . First, the action of G on X induces an isotropy representation of G x on the tangent space T x X.…”
Section: Semistable Spacesmentioning
confidence: 99%
“…In [HS05] it is shown that S G (M ip ) is open when U is abelian. Here we give a proof of a more general result.…”
Section: Introductionmentioning
confidence: 99%